Model Sinektik Berbasis Ekokritik Sastra dalam Pembelajaran Menulis Teks Cerpen Siswa SMA Padang - Mita Domi Fella Henanggil; Yulianti Rasyid; Diantri Seprina Putri; Aditya Rachman (Faculty of Languages and Arts, Universitas Negeri Padang, 2023)
Writing skill is still the most difficult language skill among the four language skills. Writing skills require a process approach. In addition, creativity is an important aspect that must exist. One of the things that can be done to foster creativity, especially in writing classes, is to take creative steps contained in the synectic model. Synectic model raises syntax or steps that can direct thinking to think creatively. Creative steps will produce creative work as well. The synectic model with its basis in literary ecocriticism is of course the right choice to produce interesting short story literary works, full of creativity, and good criticism of the surrounding environment. This research is a quantitative research with a quasi-experimental type of research. The data collected is in the form of numbers. The purpose of this study was to look at the effect of using a synectic model based on literary ecocriticism in learning to write short story texts at school. The research data is short story texts that have been written by students. The results of the study show that there is an effect of using the literary ecocritic-based synectic model in writing short story texts.